Physical and toxicological properties of water treatment residue incorporated clay bricks / Puspanathan Krishnan - Puspanathan, Krishnan (2021)
Water Treatment Residue (WTR) disposal is a major issue in most parts of the world as well as in Malaysia due to its huge quantity. It is estimated that WTR weighs at 2 % of the total treated water quantity. In 2014, Malaysia produces 16,000 million L/d (MLD) of drinking water. Only 30 % of the Malaysia Water Treatment Plant operates with sludge treatment and treated effluent discharge to water course. The characteristic of the WTR depends on the quality of river water (water source) and the type of coagulants used. Common chemical coagulants used in Malaysia are alum (AlSO4) and poly-aluminum chloride (PAC). These chemical coagulants generates residue which containing aluminium which is classified as scheduled wastes (SW 204) under Environmental Quality Act 1974, Environmental Quality (Schedule Wastes) Regulation 2005. This research study focused to reuse a portion of WTR as raw material which can be used as plasticizer with laterite earth for clay bricks manufacturing process. The research project investigated physical and mechanical properties of WTR Bricks such as compressive strength, efflorescence effects, bulk density, water absorption, weight reduction according to BS/EN Standard, loss of ignition, toxicity and ecotoxic analysis. The results indicates best combination for laboratory size brick of 40% WTR – 60% Laterite and commercial size bricks 30% WTR – 70% Laterite.”.